2011
DOI: 10.1515/crelle.2011.008
|View full text |Cite
|
Sign up to set email alerts
|

A trace formula for varieties over a discretely valued field

Abstract: Abstract. We study the motivic Serre invariant of a smoothly bounded algebraic or rigid variety X over a complete discretely valued field K with perfect residue field k. If K has characteristic zero, we extend the definition to arbitrary K-varieties using Bittner's presentation of the Grothendieck ring and a process of Néron smoothening of pairs of varieties.The motivic Serre invariant can be considered as a measure for the set of unramified points on X. Under certain tameness conditions, it admits a cohomolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 42 publications
(43 reference statements)
0
23
0
Order By: Relevance
“…We expect that the trace formula is valid if X is geometrically connected and cohomologically tame, and X(K t ) non-empty. We've proven this if k has characteristic zero [Ni11,6.5], if X is a curve [Ni11,§7], and if X is an abelian variety [Ni09b, 2.9]. Our formula for the error term shows that (assuming the existence of an sncd-model), our conjecture is equivalent to a partial generalization of Saito's criterion to arbitrary dimension (Question 4.2.4).…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…We expect that the trace formula is valid if X is geometrically connected and cohomologically tame, and X(K t ) non-empty. We've proven this if k has characteristic zero [Ni11,6.5], if X is a curve [Ni11,§7], and if X is an abelian variety [Ni09b, 2.9]. Our formula for the error term shows that (assuming the existence of an sncd-model), our conjecture is equivalent to a partial generalization of Saito's criterion to arbitrary dimension (Question 4.2.4).…”
Section: Introductionmentioning
confidence: 86%
“…In particular, s(X) = 0 if X(K) = ∅, since in this case, X is a weak Néron model of itself. In [Ni11], we've shown that under a certain tameness condition on X, the value s(X) admits a cohomological interpretation in terms of a trace formula. To study this formula, we introduce the following definition.…”
Section: 2mentioning
confidence: 99%
See 3 more Smart Citations